An integron of class 1 is present on the plasmid pCG4 from gram-positive bacterium Corynebacterium glutamicum - Nesvera, J; Hochmannová, J; Pátek, M (FEMS microbiology letters, 1998)
The streptomycin/spectinomycin resistance determinant of the 29-kb plasmid pCG4 from Corynebacterium glutamicum was found to be a part of a typical class 1 integron. The sequence analysis revealed that the integron (designated InCg) identified in this Gram-positive bacterium is almost identical to the integron InC present on the plasmid pSA1700 from the Gram-negative bacterium Pseudomonas aeruginosa. Differences in only two base pairs were found in the 3.8-kb sequence. One base substitution (G-->C) is present in the streptomycin/spectinomycin resistance determinant which is thus identical to the aadA2a gene from the integron In6 of the broad-host-range plasmid pSa. The other one (C-->G) is present in the extended -10 region of the integron promoter involved in expression of the antibiotic resistance gene. It was shown that this novel version of the integron promoter displays five times higher activity in both C. glutamicum and Escherichia coli than the original one.
Keywords: Bacterial Proteins; Corynebacterium; Integrases; Plasmids; sekvence nukleotidů; Molecular Sequence Data; molekulární sekvence - údaje; Streptomycin; bakteriální proteiny; Pseudomonas aeruginosa; Drug Resistance, Microbial; streptomycin; integrasy; antibiotická rezistence; plazmidy; Base Sequence; Escherichia coli